Основы безопасной работы на кривошипном прессе - Корниенко, Е. В. (ХНУРЭ, 2012)
This work is devoted to the safe operation of presses used for stamping various parts. The paper gives a brief description of the existing presses. The methods of ensuring safe operation and a safe working environment